The Role Of KPAI On The Human Rights of Children as Victims of Rapes In Educational Environments - Dina Indriyani; Joko Setiyono (Green Publisher Indonesia, 2022)
The purpose of this paper is to be able to find out about what are the forms of violations of rape against children in the educational environment and explain how the role of the KPAI in the human rights of children who are victims of rape in the educational environment. The approach method used is normative juridical with qualitative writing. The educational environment is one of the places that are prone to rape of children which is known together that the educational environment should be a safe and comfortable place for children to seek knowledge. The role that KPAI has on the human rights of children as victims of rape in the educational environment is expected to make the child still able to become the next generation of the Indonesian nation by means of mental, physical, and social recovery from the child in order to recover, through Law Number 17 of 2016 Second Amendment to Law Number 23 of 2002 concerning Child Protection with its basic form such as enabling victims to continue their education without having any fear of acts of rape that have occurred before in their educational environment